Curcumin Inhibits Growth of Human NCI-H292 Lung Squamous Cell Carcinoma Cells by Increasing FOXA2 Expression - Tang, Lingling; Liu, Jinjin; Zhu, Linyun; Chen, Qingge; Meng, Ziyu; Sun, Li; Hu, Junsheng; Ni, Zhenhua; Wang, Xiongbiao (Frontiers in Pharmacology, 2018)
Lung squamous cell carcinoma is a common histological lung cancer subtype, but unlike lung adenocarcinoma, limited therapeutic options are available for treatment. Curcumin, a natural compound, may have anti-cancer effects in various cancer cells, but how it may be used to treat lung squamous cell carcinoma has not been well studied. Here, we applied curcumin to a human NCI-H292 lung squamous cell carcinoma cell line to test anti-cancer effects and explored underlying potential mechanisms of action. Curcumin treatment inhibited NCI-H292 cell growth and increased FOXA2 expression in a time-dependent manner. FOXA2 expression was decreased in lung squamous cell carcinoma tissues compared with adjacent normal tissues and knockdown of FOXA2 increased NCI-H292 cells proliferation. Inhibition of cell proliferation by curcumin was attenuated by FOXA2 knockdown. Moreover inhibition of STAT3 pathways by curcumin increased FOXA2 expression in NCI-H292 cells whereas a STAT3 activator (IL-6) significantly inhibited curcumin-induced FOXA2 expression. Also, SOCS1 and SOCS3, negative regulators of STAT3 activity, were upregulated by curcumin treatment. Thus, curcumin inhibited human NCI-H292 cells growth by increasing FOXA2 expression via regulation of STAT3 signaling pathways.